Splenic echinococcosis.: Seven new observations. - Bogliaccini, Gustavo; Ruso, Luis; Olivera, Daniel (Cirugía del Uruguay, 1988)
The author presents seven new cases of splenic echinococcosis, comments pathological and diagnostica! aspects, and insists on the importance of echography as an effective method in order to establish the cystic nature of splenomegalia. Cystectomy with spleen conservation is presented as the ideal tactic, accepting it is not always feasible, depending on local conditions and the atrophy degree of splenic parenchyma.